Effectiveness Of Traditional Games Against Motivation Of Tarogong Football Athletes In Following Warm-Up - Idris Supriadi; Devaron Suardi; Ira Asyura (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
Athletes motivation in following warm-up should be considered. Athletes can continue to be the top of the performance and the achievements of the club achieved to the maximum. But there are still many athletes don’t understand the importance of warming up for itself. The same thing happens, the dominant Tarogong FC football athletes are still lazy in warm up. This has a negative effect or impact on the athlete's training program. Among them athletes can experience sports injuries such as muscle cramps, sprains, and so on because various functions of the body's organs are not ready. Therefore, the role of a coach is needed to find a solution how to motivate the athlete to want and be happy when warming up, one of them with traditional games. In statistical analysis for the processing of PTK data , the results showed a significant difference between motivation in cycle 1 and motivation in cycle 2, where the average motivation during cycle 1 is 90.98 and the current motivation average in cycle 2 is 99.55. Thus, there is an increase in the motivation of Tarogong FC football athletes with traditional games in following warm-up.